Aplikasi Program HEC-RAS 5.0.7 untuk Pemodelan Banjir di Sub-sub DAS Martapura Kabupaten Banjar - Muhammad Ramadhani Wijayanto; Noordiah Helda (Fakultas Teknik, 2022)
Rainfall data is one of cause factor for flooding in some areas in Indonesia. An extreme rainfall event occurred in the end of 2020 until early 2021 have resulted a severe flooding in West Martapura District, Banjar Regency, South Kalimantan Province. As a tributary to Barito River, Martapura River experienced high water level that gave negative impact to the surrounding areas. HEC-RAS (Hydrologic Engineering Center's River Analysis System) 5.0.7 software combined with ArcGIS 10.8 were applied to model flooding spatially. Mononobe method was used to calculate rainfall intensity for 5-year, 50-year, and 100-year return periods. From the results of the flood modeling, the maximum flood water level elevation was obtained as deep as 3.8 m (5-year return period), 5.2 m (50-year return period), and 9.6 m (100-year return period) with a maximum flood discharge of 34.84 m3/s (5-year return period), 81.68 m3/s (50-year return period), and 142.64 m3/s (100-year return period), respectively.